2013
DOI: 10.1016/j.visres.2013.01.006
|View full text |Cite
|
Sign up to set email alerts
|

The visual discrimination of negative facial expressions by younger and older adults

Abstract: Previous research has demonstrated that older adults are not as accurate as younger adults at perceiving negative emotions in facial expressions. These studies rely on emotion recognition tasks that involve choosing between many alternatives, creating the possibility that age differences emerge for cognitive rather than perceptual reasons. In the present study, an emotion discrimination task was used to investigate younger and older adults' ability to visually discriminate between negative emotional facial exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 30 publications
3
27
1
Order By: Relevance
“…However, in naturalistic environments, emotions are not always overtly evident, especially when they are not directed towards another person, suggesting that these previous experimental paradigms may not be ecologically valid. This hypothesis is supported by a recent study suggesting that older participants do not always exhibit deficits when discriminating low intensity, negative facial expressions (Mienaltowski et al, 2013). Moreover, it is plausible that in these previous studies, participants were not extracting emotion information from the stimuli per se, but instead selecting responses on the basis of learned and familiar actions.…”
mentioning
confidence: 69%
“…However, in naturalistic environments, emotions are not always overtly evident, especially when they are not directed towards another person, suggesting that these previous experimental paradigms may not be ecologically valid. This hypothesis is supported by a recent study suggesting that older participants do not always exhibit deficits when discriminating low intensity, negative facial expressions (Mienaltowski et al, 2013). Moreover, it is plausible that in these previous studies, participants were not extracting emotion information from the stimuli per se, but instead selecting responses on the basis of learned and familiar actions.…”
mentioning
confidence: 69%
“…In an extensive review, it was noted that there is a consistent tendency for healthy elderly individuals to identify EFEs worse than younger subjects [13], especially when it comes to EFEs with negative valence like fear, anger and sadness, a tendency that has been corroborated elsewhere [15,16]. Cognitive deficits, such as MCI, seem to worsen the difficulties in recognizing EFEs [17,18], specifically the identification of fear [19,20] and anger [21], and in patients with dementia, such as those with AD, the ability to identify emotions is lost as the disease progresses [22,23].…”
Section: Introductionmentioning
confidence: 85%
“…In fact, Mienaltowski and colleagues (2013) found that older and younger adults had similar performance in recognizing emotions at high intensity when comparing pairs of emotions. To ensure relatively high emotion recognition of virtual agent faces, designers may want to consider displaying facial emotions at medium (60%) intensity or higher.…”
Section: Discussionmentioning
confidence: 95%
“…However in one study, where the cognitive demands of the task were minimized, age-related differences in recognizing anger and sadness (Mienaltowski et al, 2013). …”
Section: Introductionmentioning
confidence: 99%